2021
DOI: 10.3390/ijms23010249
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Mesenchymal Stem Cells for Enhanced Therapeutic Utility in Ischemic Vascular Diseases

Abstract: Mesenchymal stem cells are multipotent stem cells isolated from various tissue sources, including but not limited to bone marrow, adipose, umbilical cord, and Wharton Jelly. Although cell-mediated mechanisms have been reported, the therapeutic effect of MSCs is now recognized to be primarily mediated via paracrine effects through the secretion of bioactive molecules, known as the “secretome”. The regenerative benefit of the secretome has been attributed to trophic factors and cytokines that play neuroprotectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 196 publications
(220 reference statements)
0
3
0
Order By: Relevance
“…Tian et al (2022) highlighted the research on tissue engineering of blood vessels using AD-MSCs as seed cells and self-assembled nano-polypeptide hydrogel for 3D printing of biological tissues [ 116 ]. These things considered, other studies have shown that MSCs can promote blood vessel formation and improve tissue perfusion in conditions such as myocardial infarction (MI) and hind limb ischemia [ 117 , 118 , 119 ]. In a study, MSCs were investigated in a murine model of hind limb ischemia.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Tian et al (2022) highlighted the research on tissue engineering of blood vessels using AD-MSCs as seed cells and self-assembled nano-polypeptide hydrogel for 3D printing of biological tissues [ 116 ]. These things considered, other studies have shown that MSCs can promote blood vessel formation and improve tissue perfusion in conditions such as myocardial infarction (MI) and hind limb ischemia [ 117 , 118 , 119 ]. In a study, MSCs were investigated in a murine model of hind limb ischemia.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…For instance, GDF11 plays a therapeutic role in cardiovascular system diseases and nervous system diseases via the regulation of MSCs and neural stem cells (NSCs). MSCs can be used for treating ischemic diseases to promote angiogenesis has been extensively carried out (Figure 2C) (57)(58)(59). However, the regulatory function of GDF11 on NSCs are controversial.…”
Section: Stem Cellsmentioning
confidence: 99%
“…Improving glycemic control following prolonged periods of retinal exposure to hyperglycemic stress, however, can still cause non-reversible effects of previous retinal microvascular damage. Laser or intravitreal treatments are usually performed when there are signs of active DR. ADSCs have been suggested to provide protective effects against retinal ischemic damage [98] and to retinal extracellular vesicles [99].…”
Section: Future Potential For Adscs In Retinal Diseasesmentioning
confidence: 99%